ChemInform Abstract: Two‐Step Synthesis of 2‐Aminoindolizines from 2‐Alkylpyridines. Issue 12 (March 2015) - Kucukdisli, Murat; Opatz, Till
Abstract 5‐Exo‐dig cyclization of 2‐alkyl‐1‐(1‐cyanoalkyl)pyridinium triflates offers a convenient method for the synthesis of 2‐aminoindolizines.